Green energy and its role in the state security system - I. A. Prudnikov; A. M. Rotar (Путеводитель предпринимателя, 2022)
According to authoritative experts in the financial sector, the final transition to a «green» economy around the world will help to move to sustainable development, which will help to get rid of poverty on the largest scale that humanity has known before. To improve and systematically accumulate natural capital (fish, soil, water resources, forest), it is necessary to correctly redistribute private and public investment funds. This can be achieved by creating acceptable conditions and the necessary political reforms.The highest priority business tasks at the moment are the development of special technologies that provide for a closed cycle, as well as a gradual annual reduction in the carbon emissions of enterprises.